Artificial Intelligence in Healthcare: Current Trends and Emerging Technologies - Sherani, Abdul Mannan Khan; Khan, Murad (CV. Multi Kreasi Media, 2024)
Many fields, and especially the healthcare sector that is many folds complex, are currently on the brink of disruption by AI. This piece examines the present and emerging kinds and applications of AI in the healthcare context, such as diagnostic, precise, prescription and virtual assistant IPs. Several aspects of applying AI technologies have already made significant impacts on the healthcare sector such as: Huge amount of data, correct diagnosis, treatment decisions for every specific case. However to advance and apply AI fairly and efficiently some issues that faced AI included integration, no standardization, financial issues, and privacy and bias problem. Depending on the recommendation of artificial intelligence such as machine learning, deep learning, natural language processing, and robotic surgery a long-awaited expectation comes with the issue of the improvement of the rate of health practice. The appropriateness of the AI for the betterment of health care in the future has been magnificently observed in PM, WI, and CT. Wearable technology and more, importantly, the constant surveillance by artificial intelligence can be a much better method in many such circumstances. Nevertheless, there are controversies connected with such a trust issue and the adoption among health care providers as main difficulties which need to overcome. AI presents the health sector with the prospects of a new style of, novel, optimal and affordable care regardless of the difficulties stated above. Thus, this paper concluded that for healthcare proactively benefit from AI, this sector requires fixing the technical, ethical and legal issues with an aim of improving the patients’ diagnosed and the health systems globally.